The lettuce that cleans water! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Jean-Pierre Bayala, in Burkina Faso, has found a simple, effective and beneficial way to clean waste water from local handicraft workshops using the water lettuce (Pistia stratiotes). Simple, because it only needs four tanks. Effective, because the...